Photostability of PMMA-TiO2 micro composites and PMMA-TiO2 nano composites - Jaafer, H. I. (Iraqi Journal of Physics, 2009)
Comparison for the optical energy gap between purePMMA , PMMA-TiO2 micro composites and PMMA-TiO2 nanocomposites have been investigated under uv – radiation , theeffect of time irradiation (0,6,12,24,48,72,96 and 120) have beenstudied for these specimens to study the photic stability .Theresults show that the photostability of the PMMA-TiO2nanocomposite is higher than that of the pure PMMA andPMMA-TiO2 micro composite under UV-light irradiation